The Effectiveness of The Bandar Lampung Government's Strategy In Realizing A Child-Friendly City - Burhibani; Feni Rosalia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
Cases of violence against children are tending to increase, indicating a diminishing sense of safety for children. The issue of children as a vulnerable group to acts of violence requires attention and concerted efforts from all stakeholders. Cases of child abuse are difficult to detect because of the limited number of people reporting them, leading to a likelihood of underreported incidents. Every child has the right to develop according to their potential, receive education, rest and recreation, and participate in all cultural activities. Children also have the right to be protected from economic and sexual exploitation, discrimination, violence, and even mediation (including physical or mental disabilities, refugees, and orphans). To fulfill these rights and protect children, and specifically to build initiatives of district/city governments aimed at transforming the Convention on the Rights of the Child from a legal framework into the definition, strategies, and development interventions, in the form of policies, programs, and development activities aimed at fulfilling children's rights and protection in a specific district/city area. The type of research and the approach used in this study is a quantitative approach with Descriptive Analysis research methods, which aims to describe and analyze the subjects under investigation. It is then carefully analyzed to obtain results as conclusions of the study on the strategies of the Bandar Lampung city government in preventing acts of violence against middle school-aged children in realizing a child-friendly city. This research is conducted in the city of Bandar Lampung.